Literature Review: Factors Influencing Organizational Commitment Among Employees - Dewi, Fitriana; Izzati, Umi Anugerah (Psikologi Prima, 2025)
Commitment in an organization is one of the key elements that contribute to organizational sustainability and effectiveness. High commitment from employees can increase productivity, reduce employee turnover, and strengthen loyalty to the organization. This article aims to analyze the core theories related to organizational commitment and identify various factors that influence it by using a Systematic Literature Review (SLR) approach. Through the analysis of various previous studies, it is found that several factors, including individual, job, and organizational factors, affect organizational commitment. In addition, various industry sectors also play a role in influencing the level and type of organizational commitment. The findings of this research are expected to provide a deeper understanding for academics and practitioners, enabling them to improve organizational commitment in various work environments.